Design of a smart device to reduce the time of assistance of elderly people that suffered an accident. - Cordero Aguilar, Nahomi (2024)
Falls are the second cause of death worldwide, with elderly people being the ones who suffer them the most. Based on the above, Auximax was created as an user-friendly intelligent device for daily use. This intelligent device has the capacity to reduce the time for assistance in an accident through an automatic alarm and therefore reduce sequels or consequences due to falling down, blows, injuries or any physical condition of similar nature.The device has a heart rate monitor. and an intelligent alarm capable of detecting sudden movements or risk situations based on the patient's cardiac condition, such device counts with a cell phone interface for easy access to family members and caregivers, and a graphic interface that allows visual information helping both the elderly and the caregiver; meaning that any of them can monitor what is happening before any given situation in real time based on the heart rate level of the user since a racing heart is a warning sign before, during and after any risk situation. It is important to highlight that the main impact of using this smart device is to ensure a user-friendly source of help and at the same time reduce auxiliary response times for elderly populations who have conditions such as diabetes, hypertension, dementia, anxiety, etc which in a fall accident could be victims of major consequences due to these pathologies.